Taxa de mortalidade relacionada à prática da pesca esportiva do cichla spp. na região do médio Rio Negro, Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The expansion of recreational fishing in Brazil started in the 1990 s, when more and more people came to the Amazon in search of peacock bass (Cichla spp.). The behavior of this cichlid, which attacks lures, is especially exciting for anglers. The middle Negro River has become one of the most popular areas of sport fishing of the world, where the largest peacock bass can be found. The importance of catch-and-release fishing as an sustainable fishing strategy has been shown to directly help conserve peacock bass fish stocks in the region. In this study, peacock bass mortality was evaluated in relation to catch-and-release fishing, comparing two types of artificial lures: the jig and a traditional middle-water type. Fish, samples were collected in January/February and October/November of 2012 in the Unini River, a right margin tributary of the Negro River, in the municipal region of Barcelos in Amazonas State. A total of 191 peacock bass were caught, 90 by jig lure and the rest by the middle-water lure. Both fish groups were submitted to experimental confinement during a period of three days. In both groups, 30 fish were confined individually and 60 confined collectively. Additionally, 11 fish from the second group had radio transmitters attached to be used in telemetry. The mortality rate was calculated for each type of lure and type of confinement. No mortality was encountered for the group caught with a jig beat lure. In comparison, the middle-water lure showed a mortality rate of 1.66% for the collective confinement and 18.18% for the monitoring involving telemetry. For both types of lures, no mortality was observed for fish confined individually. The data was plotted using a Kruskal-Wallis variance analysis that showed values of X2 (1.179) = 0,502 and p= 0,478 for confined environments. The same test show values of X2 (1.179) = 1,005 e p= 0,316 for the different lures. The results indicated that neither confinement type or lure type had a significantly negative impact on the peacock bass mortality rate from the catch-and-release fishery, demonstrating that catchand- release fishing has a very small impact on peacock bass mortality. Therefore, this type of recreational fishing is beneficial as a strategy to help conserve peacock bass fish stocksfishery
Keywords: Pesque-solte; Tucunaré; Pesca amadora; Mortalidade de peixes; Catch-and-release fishing; Peacock bass; Amateur fishery; Fish Mortality; RECURSOS PESQUEIROS E ENGENHARIA DE PESCA